2013
DOI: 10.1177/0888406413497485
|View full text |Cite
|
Sign up to set email alerts
|

Preparation for Inclusion in Teacher Education Pre-Service Curricula

Abstract: Inclusion of students with disabilities has been practiced and advocated for more than two decades in the United States. This practice involves the placement of students with disabilities in a general education classroom for part or all of the day, and the primary instructor is a general education teacher in collaboration with a special education teacher. The authors reviewed coursework related to inclusion provided to pre-service elementary teachers during their teacher preparation programs. A total of 109 el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
68
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(75 citation statements)
references
References 34 publications
5
68
0
2
Order By: Relevance
“…Participants further revealed that in-service training of regular teachers in teaching and learning strategies of children with ASD would facilitate the inclusion of these children in mainstream classrooms. This finding aligns with previous studies which have found that teachers need professional development in order to be informed and knowledgeable about ASD and about individualisation strategies for children with ASD in mainstream classrooms (Allday et al 2013;Humphrey and Parkinson 2006;Lynch and Irvine 2009;Sheffield 2008;Winn and Blanton 2005). Similarly, Humphrey (2008), Lindsay and McPherson (2012), and Maich and Belcher (2012) found that grounding teacher in-service training in the unique needs of children with ASD facilitates inclusion of these children in mainstream classrooms.…”
Section: Discussionsupporting
confidence: 90%
“…Participants further revealed that in-service training of regular teachers in teaching and learning strategies of children with ASD would facilitate the inclusion of these children in mainstream classrooms. This finding aligns with previous studies which have found that teachers need professional development in order to be informed and knowledgeable about ASD and about individualisation strategies for children with ASD in mainstream classrooms (Allday et al 2013;Humphrey and Parkinson 2006;Lynch and Irvine 2009;Sheffield 2008;Winn and Blanton 2005). Similarly, Humphrey (2008), Lindsay and McPherson (2012), and Maich and Belcher (2012) found that grounding teacher in-service training in the unique needs of children with ASD facilitates inclusion of these children in mainstream classrooms.…”
Section: Discussionsupporting
confidence: 90%
“…In the mid 1980"s when the REI began in the United States, both proponents and opponents of inclusion movements shared a common concern about the general educational system not being prepared to meet the diverse educational needs of students with disabilities and to remediate their learning deficiencies, especially general education teachers. The major concern was whether or not general education teachers were prepared for successful inclusive education, because successful inclusion necessitates highly qualified teachers who were ready to meet the needs of exceptional learners (Allday, Neilsen-Gatti, & Hudson, 2013;Harvey, Yssel, Bauserman, & Merbler, 2010;Smith, Polloway, Patton, & Dowdy, 2012;Thompkins & Deloney, 1995). The purpose of this study is, therefore, to investigate how much inclusive education has progressed toward the goal of providing the best education to students with disabilities.…”
Section: Common Concernsmentioning
confidence: 99%
“…Second, as mentioned in the introduction and literature review of this article, historically, teacher education programs have done a poor job of blending general and special education in order to properly prepare general education teachers to work in inclusive classrooms and in collaboration with special education teachers (Allday et al, 2013;Scruggs & Mastropieri, 1996;Smith & Smith, 2000). Some of the SAS teachers' comments during interviews, however, could lead one to believe that the aforementioned trend in teacher education may be shifting toward an interdisciplinary approach.…”
Section: Discussionmentioning
confidence: 86%
“…And rightfully so. According to Allday, Neilsen-Gatti, and Hudson (2013), most educator preparation programs at colleges and universities around the country "are not offering extensive coursework on working in inclusive environments" (p. 308).…”
Section: Professional Developmentmentioning
confidence: 99%